Sexo en la pantalla, sexo en las butacas: una inmersión-comprensión en las penumbras de las salas X - Pineda, Ramón (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
In the half-light of the X rooms men transit through several sexual practices that affect the power relations that hegemonic masculinity norms exert upon the body. The identification of such practices and transits in order to elaborate a master’s thesis titled Cuerpos obscenos, cuerpos transeúntes, cuerpos gozados (masculinidades en las penumbras de las salas X de Medellín) [Obscene bodies, transient bodies, joyful bodies (masculinities in the half-light of Medellín’s X rooms)] has required the author a patient and vast immersion. This essay deals with how a reported has created synergies between the research techniques of a reporter and of a social scientist in order to achieve a comprehension of the phenomenon that happens there. During a one-year period he was another actor and has played a role in this half-light scenery, and has identified protocols, constants and did in-depth interviews with eight protagonists of this “porn” movie of real life that happens on a daily basis before others, the ones of hyperbolic fiction created by the adult entertainment industry.